2016
DOI: 10.1021/acs.iecr.6b01493
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Silver Cathode for Electrochemical Deoxygenation of Seawater for Enhanced Oil Recovery

Abstract: Seawater injection into reservoirs is a common method to enhance oil recovery. In order to avoid corrosion in pipes, the oxygen has to be removed from the seawater. This study focuses on the use of silver cathodes in electrochemical cells for oxygen removal, and the physical parameters that affect the efficiency of this process. Three electrochemical cells have been constructed and tested with packed bed cathodes made up of pure silver particles and silver plated brass spheres. Experimental results showed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…This method avoids the use of additional chemicals and utilizes only seawater as an electrolyte. The electrochemical system with a silver cathode for oxygen removal works efficiently on both the laboratory scale and the industrial scale, as previously reported by Dotel et al [1,2].…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…This method avoids the use of additional chemicals and utilizes only seawater as an electrolyte. The electrochemical system with a silver cathode for oxygen removal works efficiently on both the laboratory scale and the industrial scale, as previously reported by Dotel et al [1,2].…”
Section: Introductionsupporting
confidence: 76%
“…The catholyte for the tests was 0.5 M NaCl (pH range 6-7); however, during stabilization before experiments, the acidic anolyte made the stagnant catholyte acidic (pH 5), and the alkaline anolyte made the catholyte slightly alkaline (pH 9). In our previous study [1], the pH of the anolyte that was stagnant decreased significantly from pH 8.00 to pH 2.16. Thus, for an industrial-scale deoxygenation cell, it is recommended to avoid keeping the anolyte stagnant.…”
Section: Assessment Of Anolytes For Industrial Deoxygenation Cellmentioning
confidence: 73%
“…The design of the electrochemical cell is based on experiences from the lab scale setup in our previous work . The cell was designed in such a way that a uniform flow of water was ensured throughout the cathode section.…”
Section: Methodsmentioning
confidence: 99%
“…The use of an electrochemical process for the removal of oxygen from seawater is an alternative method that avoids the disadvantages described for the other methods. The oxidation of water to yield hydroxium ion and oxygen, and the reduction of oxygen to water are the basis for deoxygenation of water. The main reactions at the two electrodes are two opposite directed reactions:…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation